2000
DOI: 10.1016/s0378-1097(00)00439-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of defined amino acid residues to the immunogenicity of recombinant Escherichia coli heat-stable enterotoxin fusion proteins

Abstract: We investigated whether the toxicity-associated receptor-binding domain of the non-immunogenic Escherichia coli heat-stable enterotoxin (STh) as a fusion with a carrier protein and the inclusion of an appropriate spacer are critical factors for eliciting antibody responses against the native toxin. The immunological properties of three toxic and one non-toxic fusion proteins, consisting of STh N-terminally joined to the C-terminus of the major subunit ClpG of E. coli CS31A fimbriae, were compared. In contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Therefore, STa alone is unable to induce anti-STa immunity in hosts. Human STa protein became immunogenic when it was linked to a carrier protein chemically (22) or, more often, genetically (4,9,17,31,33), as the genetic fusion approach showed precise definition of the final products, easy manipulation, and low cost (9). When a native hSTa gene was genetically fused to a native human eltA gene (encoding the LT A subunit) or eltB gene (encoding the LT B subunit) or to an E. coli colonization factor antigen (CFA) gene, the fusion products were recognized by anti-STa antibodies (5,31,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, STa alone is unable to induce anti-STa immunity in hosts. Human STa protein became immunogenic when it was linked to a carrier protein chemically (22) or, more often, genetically (4,9,17,31,33), as the genetic fusion approach showed precise definition of the final products, easy manipulation, and low cost (9). When a native hSTa gene was genetically fused to a native human eltA gene (encoding the LT A subunit) or eltB gene (encoding the LT B subunit) or to an E. coli colonization factor antigen (CFA) gene, the fusion products were recognized by anti-STa antibodies (5,31,33).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we need to attenuate the pSTa toxicity. It has been reported that shorter synthetic hSTa peptides or hSTa with disulfide bonds disrupted showed toxicity reduction (4,5,19,40,46,47). Moreover, several shorter synthetic hSTa peptides that had the 12th, 13th, or 14th amino acid residue replaced showed a great reduction in toxicity (46,47).…”
mentioning
confidence: 99%
“…Although it has been suggested that STa needs to retain some toxicity in order to become immunogenic when carried by a carrier protein (3,35,36), other studies clearly indicated that nontoxic STa antigens in fusion formats elicited neutralizing antibodies (18,19,20,28,46). It was demonstrated that synthetic mutated pSTa (pSTa N11P , pSTa Y18N ), when chemically cross-linked to an LT B subunit or porcine IgG molecules, elicited anti-STa antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Detoxifying ST. Detoxification of ST can be achieved, at least in part, by genetic fusion or chemical conjugation, but it has often been combined with mutagenesis (2,35,39). Several mutants with effects on toxicity have been reported and are summarized in Fig.…”
Section: St Vaccinologymentioning
confidence: 99%
“…One challenge in the development of an ST vaccine is to separate toxicity from antigenicity (2). Due to the small size of ST, it is likely that single-amino-acid substitutions which reduce toxicity may also impinge on the resulting toxoid's ability to induce neutralizing antibodies.…”
Section: St Vaccinologymentioning
confidence: 99%